2019
DOI: 10.4054/demres.2019.41.11
|View full text |Cite
|
Sign up to set email alerts
|

A framework for the prospective analysis of ethno-cultural super-diversity

Abstract: BACKGROUNDPressures to keep immigration rates at relatively high levels are likely to persist in most developed countries. At the same time, immigrant cohorts are becoming more and more diverse, leading host societies to become increasingly heterogeneous across multiple dimensions. For scholars who study demographic or socio-economic behaviours, the need to account for ethno-cultural "super-diversity" brings new challenges. OBJECTIVEThe main objective of this paper is to present a framework for the prospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 70 publications
0
20
0
Order By: Relevance
“…Microsimulation models, though heavily dependent on data, are powerful tools that can inform research in an innovative way, for a broad range of issues. The models presented in this paper are built according to a research framework (Bélanger et al 2019) that aims to assess the impact of population dynamics in Western countries and the changes that are likely to happen in terms of ethno-cultural and sociodemographic characteristics. Capable of projecting the population according to numerous variables, these models generate workforce-relevant results to guide policymakers in their decisions regarding immigration policy and the conditions for education skills formation.…”
Section: Resultsmentioning
confidence: 99%
“…Microsimulation models, though heavily dependent on data, are powerful tools that can inform research in an innovative way, for a broad range of issues. The models presented in this paper are built according to a research framework (Bélanger et al 2019) that aims to assess the impact of population dynamics in Western countries and the changes that are likely to happen in terms of ethno-cultural and sociodemographic characteristics. Capable of projecting the population according to numerous variables, these models generate workforce-relevant results to guide policymakers in their decisions regarding immigration policy and the conditions for education skills formation.…”
Section: Resultsmentioning
confidence: 99%
“…Our conclusions are based on the application of a new tool-the LSD-USA microsimulation model-to better understand the likely long-run implications of immigration policy scenarios for the skill levels of the future labor force populations in the United States. The LSD-USA model has many advantages over more traditional types of projection models (Bélanger et al 2019a). For example, it accounts for multiple socioeconomic, cultural, and demographic characteristics, including mother's educational attainment, in the computation of the probability of the occurrence of life course events and educational attainments.…”
Section: Discussionmentioning
confidence: 99%
“…Next, we describe the inputs we used to simulate the immigration scenarios for this paper. Detailed technical descriptions of the general model (Bélanger and Sabourin 2017; Lutz and Belanger 2017; Marois, Sabourin and Bélanger 2017) and its various applications (Bélanger et al 2019a) can be found elsewhere. A detailed description of the US version of the model is also available online (Bélanger et al 2019b).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Centre for Expertise on Population and Migration (CEPAM) aims to investigate the impacts of immigration on the future population in European Union. Full details of the architecture of CEPAM-Mic are available elsewhere 54 , 56 , 59 , 63 , 64 . In brief, CEPAM-MIC is a dynamic, continuous time, event-based, and spatial microsimulation projection model programed in the Modgen language, a microsimulation programming language developed by Statistics Canada, integrated into the Microsoft Visual Studio C + + environment.…”
Section: Building Athlos-mic Microsimulation Modelmentioning
confidence: 99%